2023
DOI: 10.2147/ccid.s403732
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential Molecular Mechanism of Sijunzi Decoction in the Treatment of Non-Segmental Vitiligo Based on Network Pharmacology and Molecular Docking

Abstract: Background Non-segmental vitiligo is a common decolorized skin disease. The purpose of this study was to reveal the active components of Sijunzi decoction (SJZD) and the target genes for the treatment of non-segmental vitiligo. Methods Based on TCMSP and GEO databases, effective components and targets of SJZD in the treatment of non-segmental vitiligo were revealed by network pharmacology. GO and KEGG were used to analyze the biological functions of SJZD targets. The Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Because of its high therapeutic value, bioactive compounds in SJZD have attracted much attention (Cui et al, 2021). Several studies have revealed the key targets of sarcopenia via network pharmacology analysis, such as AKT1, AIRT1, TNF, TP53 and PPARA (Cai et al, 2023;Du et al, 2023). In our network pharmacology study, 92 active compounds of SJZD against sarcopenia were acquired.…”
Section: Discussionmentioning
confidence: 91%
“…Because of its high therapeutic value, bioactive compounds in SJZD have attracted much attention (Cui et al, 2021). Several studies have revealed the key targets of sarcopenia via network pharmacology analysis, such as AKT1, AIRT1, TNF, TP53 and PPARA (Cai et al, 2023;Du et al, 2023). In our network pharmacology study, 92 active compounds of SJZD against sarcopenia were acquired.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, investigations into specific compounds, such as kaempferol and quercetin, suggest their role in modulating PPARG expression and interacting with AKT1, pointing towards potential treatment avenues for endometrial cancer and nonsegmental vitiligo [ 22 , 23 ]. The relevance of these interactions extends to conditions like uric acid nephropathy, pneumonia, and type 2 diabetes mellitus, as demonstrated by studies using Xiezhuo Huayu Yiqi Tongluo Formula (XHYTF), Fritillariae thunbergii bulbus, and Alpinia officinarum Hance [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%